Daily life and the arts of working: The work in basic health care - Jaqueline Tittoni; Universidade Federal do Rio Grande do Sul; Rosemarie Gartner Tschiedel; Universidad Federal do Rio Grande do Sul (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2020)
This article discusses the daily work in primary health care, underscoring the role of the health teams with the schools of the community and the activities of the community health agents. It addresses everyday micropolitics as ways of thinking about real-live work in action. We focus on the ways of work, especially in the relationships that are established on the daily work, recognizing that the less seeing resistances are the most efficient.  In this study, we followed the work of two health units in two health districts in Porto Alegre-Brasil, one located in a central area of the city and the other in the peripheral area. Cartography is the methodological premise, focusing on monitoring daily processes. The monitoring was recorded in research diary and in photographic productions. It was identified that the teams produce arrangements between the prescribed goals, the working conditions and the resources of the communities. These facts occur in daily work, which involve affections and sensitivities, which are not always visible in the prescriptions and regulations that guide the work, hence the importance of their study.